Homing in hematopoietic stem cells: focus on regulatory role of CXCR7 on SDF1a/CXCR4 axis - Asri, Amir (EXCLI J, 2016)
Hematopoietic stem cells (HSCs) form a rare population of multipotent stem cells, which give rise to all hematopoietic lineages. HSCs home to bone marrow niches and circulate between blood and bone marrow. Many factors, especially SDF1a, affect the circulation of HSCs, but these have not been fully recognized. SDF1a has been shown to bind CXCR7 in addition to CXCR4 and can also function as SDF1a/CXCR4 modulator. CXCR7 plays a role in HSCs homing via SDF1a gradient and is a mediator of CXCR4/SDF1a axis. This review describes the current concepts and questions concerning CXCR7/CXCR4/SDF1a axis as an important key in hematopoietic stem cells homing with particular emphasis on CXCR7 receptor. Homing of HSCs is an essential step for successful hematopoietic stem cell transplantation.